Effect Of Exercise Therapy on Lipid Profile and Oxidative Stress Indicators in Patients with Type 2 Diabetes - Jadoon, Madeeha; Zeb, Shazia; Razaq, Sajid; Khan, Munazza; Shoaib, Muhammad; Mariyum, Sara (Journal of Rawalpindi Medical College, 2024)
Objective: To measure change in lipid profile and levels of oxidative stress by performing exercise therapy in patients with type 2 diabetes. Methods: This cross-sectional study was carried out from January 2022 to January 2023 at Hayatabad Medical Complex, Peshawar, and consisted of 35 patients with T2DM using non-probability consecutive sampling. Criteria for patient selection were a T2DM duration of at least one year and patients aged between 28-45 years with or without consent to enrol for the study. Information was gained through questionnaires, satisfaction surveys, physical assessments, and biochemical assays. Levels of lipid profiles and oxidative stress indicators were determined enzymatically from the sera obtained from the fasting blood samples and by ELISA kits. Results: This study established that exercise therapy has a beneficial effect on the lipid status of patients with type 2 diabetes. Overall cholesterol and LDL-C concentration also decreased (p = 0. 023 and p = 0. 042, respectively) thereby lowering cardiovascular risk. LDL-C adiposity levels were reduced (p = 0. 378), but desirable cholesterol levels, HDL-C, improved (p = 0. 032). Additionally, oxidative stress indicators improved: Apropos to this, serum MDA, a marker of oxidative stress, significantly reduced (p = 0. 012). The total antioxidant capacity (TAC) and the antioxidants enzymes; superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase all increased (p = 0. 021, 0. 035, 0. 022 and 0. 015) and increased the body’s ability to fight oxidative stress. Conclusion: Exercise therapy significantly improves type 2 diabetes patients' oxidative stress indicators and lipid profiles. According to the data, there was a significant decrease in triglycerides, LDL-c, HDL-c, and total cholesterol following the exercise intervention. As a result, exercise is crucial for controlling dyslipidemia, a common problem in individuals with diabetes. The improvement in metabolic health can be attributed to the protective effects of exercise against oxidative stress, as seen by the decline in MDA levels and the rise in activity of antioxidant defence-related enzymes such as superoxide dismutase, glutathione peroxidase and catalase.